Mixer-settler system for the recovery of copper and zinc from MSWI fly ash leachates: An evaluation of a hydrometallurgical process. (1st April 2017) - Tang, Jinfeng; Petranikova, Martina; Ekberg, Christian; Steenari, Britt-Marie
Abstract: Municipal Solid Waste Incineration (MSWI) fly ash contain large amounts of leachable heavy metals, and thus is classified as hazardous waste. The increased amounts of fly ash generated cause environmental issues and accumulation of valuable metals in landfills which contribute to an increased interests to recognize the ash as an urban mining target of metal resources. The high leachability of fly ash metal compounds could instead be seen as a benefit since it opens a path for metal recovery. This study reports a new potential hydrometallurgical process based on combining leaching and sequential solvent extraction to recover copper and zinc from MSWI fly ash. The investigations were carried out at bench scale and laboratory pilot scale. The pilot scale unit, operated as a counter-current mixer-settler system. The separation of copper and zinc from the acidic ash leachate was achieved using LIX860N-I and Cyanex 923, two commercial extraction reagents, respectively. The phase contact time to reach equilibrium, number of mixer-settler stages of the system and liquid to organic ratios were investigated for optimization. Removal of co-extracted metals, e.g. cadmium, iron and lead to obtain higher purity of zinc solution, was carried out using either cementation before the zinc extraction, or selective stripping with different stripping agents sequentially after extraction. An efficient recovery of the copper and zinc present in an ash leachate, more than 90% and 99% respectively, was achieved sequentially in a mixer-settler system, which comprised of two stages for copper extraction and three stages for zinc extraction. Moreover, the removal of the toxic metals lead and cadmium is reported. Highlights: A process for recovery of Cu and Zn from MSWI fly ash was developed in pilot scale. More than 90% of Cu and Zn in the leachate were recovered in separate flows. The Cd, Fe and Pb co-extracted with Zn can be removed to give a pure Zn solution. The data presented can be used to scale up the process further.